Materializing digital futures touch, movement, sound and vision - Cinque, Toija ca. 20. Jh; Vincent, Jordan Beth ca. 20./21. Jh (Bloomsbury Academic, 2022)
"Offers a way to re-evaluate deeply evocative futures in which humans and intelligent systems increasingly engage in symbiotically connected experiences via continuous flows of data and information exchanges"--
Keywords: Digitalisierung; Neue Medien; Digital media / Social aspects; Multimedia communications / Social aspects; Human-computer interaction; Aufsatzsammlung